SIFO 1991: Swedes, EC and the snuff - Swedish Institute of Public Opinion Research; United Brands (Swedish Institute of Public Opinion Research, 1994)
The special topic of this survey, carried out at the request of United Brands, is the Swedish habit of taking snuff and the treatment of this custom within the EC. The respondents were asked if they used snuff themselves and about their opinion on persons using snuff. Furthermore they were asked about their opinion on a prohibition of snuff within the EC, and if this will influence their attitude toward the EC. If Sweden should make the right to decide about snuff a condition when applying for EC-membership, and of what importance this right of self-determination is. More general questions dealt with the influence of Swedish government and parliament on the development of the country and on the development in Europe if Sweden becomes an EC-member and the opinion on a Swedish application for EC-membership. Background variables include information on gender, place of living, age, Swedish citizenship, occupation, private or public sector, trade union, income and party voted for in the general election 1988.

SIFO genomförde denna undersökning på uppdrag av United Brands under perioden 24-27 juni 1991. Frågorna ingick i SIFO-buss 91085 och utfördes i form av telefonintervju. Respondenterna fick ange om man trodde att Sveriges regering och riksdag skulle få ökat eller minskat inflytande över utvecklingen i Sverige respektive i Europa om Sverige blev medlem i EG, samt om man själv tyckte att Sverige skulle ansöka om medlemskap i EG. Undersökningen innehöll dessutom ett antal frågor om snus; huruvida man använder snus själv; inställning till andras användning av snus; hur man förhåller sig till ett snusförbud inom EG och om detta påverkar den egna inställningen till ett svenskt EG-medlemskap. Därutöver ingick ett antal bakgrundsfrågor om respondentens kön, ålder, bostadsort, medborgarskap, sysselsättning, medlemskap i fackförening, samt partival vid riksdagsvalet 1988.
SIFO 1991: Svenskarna, EG och snuset
Keywords: drinking behaviour; alkoholvanor; smoking; rökning; drug abuse; drogmissbruk och medicinmissbruk; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap; Diet and nutrition; Kost och näring